2020
DOI: 10.1038/s41586-020-2190-3
|View full text |Cite
|
Sign up to set email alerts
|

Tail-propelled aquatic locomotion in a theropod dinosaur

Abstract: Intensive research on non-avian dinosaurs in recent decades strongly suggests that these animals were restricted to terrestrial environments 1. Historical views proposing that some groups, such as sauropods and hadrosaurs, lived in aquatic environments 2,3 were abandoned decades ago 4,5,6. Recently, however, it has been argued that at least some spinosaurids, an unusual group of large-bodied Cretaceous theropods, were semi-aquatic 7,8 , but this idea has been challenged on anatomical, biomechanical, and taphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(120 citation statements)
references
References 35 publications
(36 reference statements)
4
116
0
Order By: Relevance
“…On the contrary, long transverse processes/pleurapophyses are widespread in the anterior caudal vertebrae of aquatic reptiles exhibiting lateral undulation of the tail (e.g. extant crocodylians, nothosaurs, spinosaurids, Ibrahim et al, 2020;Rieppel, 2000) and they provide important muscle attachment sites for undulation. Furthermore, the slight expansion of the neural spines of the trunk and tail vertebrae in Tanystropheus possibly indicates the presence of supraspinous ligament of some sort, but it does not provide convincing evidence that the trunk and tail were highly stiffened.…”
Section: Palaeobiology and Functional Morphology Of The Skullmentioning
confidence: 99%
“…On the contrary, long transverse processes/pleurapophyses are widespread in the anterior caudal vertebrae of aquatic reptiles exhibiting lateral undulation of the tail (e.g. extant crocodylians, nothosaurs, spinosaurids, Ibrahim et al, 2020;Rieppel, 2000) and they provide important muscle attachment sites for undulation. Furthermore, the slight expansion of the neural spines of the trunk and tail vertebrae in Tanystropheus possibly indicates the presence of supraspinous ligament of some sort, but it does not provide convincing evidence that the trunk and tail were highly stiffened.…”
Section: Palaeobiology and Functional Morphology Of The Skullmentioning
confidence: 99%
“…The spinosaurids are widely regarded as being at least partly piscivorous, and with potential affinities for aquatic habitats (e.g., Charig and Milner, 1995;Bertin, 2010;Cuff and Rayfield, 2013;Hone and Holtz, 2017;Aureliano et al, 2018;Hassler et al, 2018) although this does not exclude other prey or the occupation of other habitats (Bertin, 2010;Amiot et al, 2010a, b;Allain et al, 2012;Hendrickx et al, 2016), and likely took prey from the margins of aquatic habitats. The recent discovery of new and much more complete material has brought new data and with it new hypotheses about the biology of this animal (Ibrahim et al, 2014a(Ibrahim et al, , 2020a. Based on new finds, it has more recently been suggested that Spinosaurus was an aquatic specialist (Ibrahim et al, 2014a, 2020a, Arden et al, 2019Beevor et al, 2020) and pursuit predator of aquatic prey (Ibrahim et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of new and much more complete material has brought new data and with it new hypotheses about the biology of this animal (Ibrahim et al, 2014a(Ibrahim et al, , 2020a. Based on new finds, it has more recently been suggested that Spinosaurus was an aquatic specialist (Ibrahim et al, 2014a, 2020a, Arden et al, 2019Beevor et al, 2020) and pursuit predator of aquatic prey (Ibrahim et al, 2020a). This stands in stark contrast to previous interpretations of spinosaurid biology and, if correct, would mark out Spinosaurus (and potentially other spinosaurines) as having a unique ecology for a nonavialian theropod.…”
Section: Introductionmentioning
confidence: 99%
“…Although Juravenator does not exhibit any anatomical features indicative of an aquatic lifestyle as in Spinosaurus (Ibrahim et al . 2014, 2020) or Halszkaraptor (Cau et al . 2017), we note that its dental morphology is particularly close to that of small opportunistic predatory coelurosaurs such as Scipionyx , Microraptor and Anchiornis , which are known to have fed at least partially on fish (Dal Sasso & Maganuco 2011; Xing et al .…”
Section: Discussionmentioning
confidence: 99%